2007
DOI: 10.1107/s1600536807002966
|View full text |Cite
|
Sign up to set email alerts
|

N-[tert-Butoxycarbonylglycyl-(Z)-α,β-dehydrophenylalanylglycyl-(Z)-α,β-dehydrophenylalanyl]glycine methyl ester

Abstract: In the crystal structure of the penta­peptide Boc0—Gly1–ΔZPhe2—Gly3–ΔZPhe4—Gly5—OMe, C30H35N5O8, the values of torsion angles Φ and Ψ show the presence of two type III′β‐turns, at the ΔZPhe2 and Gly3 residues, and Gly3 and ΔZPhe4 residues. All amino acids in the peptide are linked trans to each other. Two intra­molecular N—H⋯O hydrogen bonds, between CO and NH groups, stabilize β‐turns present in the peptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…They are stabilized by 4!1 hydrogen bonds between the NH group of Á Z Phe 4 and the CO group of Gly 1 , and between the NH group of Gly 5 and the CO group of Á Z Phe 2 ( Table 2). The two -turns of type III 0 in (I) are the same as in the previously reported crystal structure of the Boc 0 -Gly 1 -Á Z Phe 2 -Gly 3 -Á Z Phe 4 -Gly 5 -OMe pentapeptide, which differs from (I) only in the methanolate group at the C terminus (Makowski et al, 2007). The molecular structure of peptide (I) is presented in Fig.…”
Section: Commentsupporting
confidence: 75%
“…They are stabilized by 4!1 hydrogen bonds between the NH group of Á Z Phe 4 and the CO group of Gly 1 , and between the NH group of Gly 5 and the CO group of Á Z Phe 2 ( Table 2). The two -turns of type III 0 in (I) are the same as in the previously reported crystal structure of the Boc 0 -Gly 1 -Á Z Phe 2 -Gly 3 -Á Z Phe 4 -Gly 5 -OMe pentapeptide, which differs from (I) only in the methanolate group at the C terminus (Makowski et al, 2007). The molecular structure of peptide (I) is presented in Fig.…”
Section: Commentsupporting
confidence: 75%
“…To the best of our knowledge, no X-ray crystallographic data of the presented molecules has yet been established. However, as discussed in the Introduction, structural studies on other dehydropeptides have revealed that insertion of the double bond in the alanine residue usually leads to the fully extended conformations with Ψ, Φ ≈ −180°, 180°. , While the introduction of ΔPhe results in folded conformations, e.g., β-turn and helices. , The calculated Φ 1 , Ψ 1 ′ angles differ significantly for the dipeptides studied here. The Φ 1 /Ψ 1 ′ angles of Boc-Gly-Δ ( Z ) Phe (127.1/–177.3°) are typical for the single dehydroresidue structures with different blocking groups, ,,, suggesting a preference of these dipeptides to form an extended C 5 conformation.…”
Section: Resultsmentioning
confidence: 66%
“…9,38 While the introduction of ΔPhe results in folded conformations, e.g., β-turn and helices. 13,39 The calculated Φ 1 , Ψ 1 ′ angles differ significantly for the dipeptides studied here. The Φ 1 /Ψ 1 ′ angles of Boc-Gly-Δ (Z) Phe (127.1/−177.3°) are typical for the single dehydroresidue structures with different blocking groups, 9,10,19,40 suggesting a preference of these dipeptides to form an extended C 5 conformation.…”
Section: Resultsmentioning
confidence: 79%
“…It has been found that in the solid state a ∆Phe residue of the Z configuration induces β-turns in short sequences [2][3][4][5][6] and a 3 10 -helix in longer ones or peptides with more than one dehydro residue. 4,[7][8][9][10][11][12][13][14][15][16][17][18][19] Similar conformational properties of ∆ Z Phe have been observed in solution by NMR 8,11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and CD, 18,19,[27][28][29][30][31][32][33][34][35][36]…”
Section: Introductionmentioning
confidence: 62%